2018
DOI: 10.1111/idj.12346
|View full text |Cite
|
Sign up to set email alerts
|

Dental health-care service utilisation and its determinants in West Iran: a cross-sectional study

Abstract: Our study indicates that dental health-care utilisation among households in the study area was influenced by a number of factors, including being socio-economically disadvantaged, self-rated poor oral health and not regularly brushing own teeth. Therefore, in this setting, dental-intervention programmes, including dental health insurance, should focus on mechanisms that can strengthen utilisation of preventive dental health-care services among disadvantaged households.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 28 publications
6
44
0
1
Order By: Relevance
“…As our study demonstrated SES, being a male, older age and being a widow or divorced as the main factors contributing to the concentration of DMFT among the worse-off in Iran, it is recommended to focus in the oral health status of these groups in order to reduce socioeconomic inequality in oral health among adults in Iran. For example, as the existing studies (e.g., [47][48][49][50]) showed prorich inequalities in health care utilization in Iran, it is recommended to expand oral health care services for these groups through publicly funded primary health care in Iran. Moreover, it should be noted that reducing socioeconomic inequalities in dental caries should be accompanied by appropriate health promotion policies that focus actions on the fundamental SES causes of dental disease.…”
Section: Resultsmentioning
confidence: 99%
“…As our study demonstrated SES, being a male, older age and being a widow or divorced as the main factors contributing to the concentration of DMFT among the worse-off in Iran, it is recommended to focus in the oral health status of these groups in order to reduce socioeconomic inequality in oral health among adults in Iran. For example, as the existing studies (e.g., [47][48][49][50]) showed prorich inequalities in health care utilization in Iran, it is recommended to expand oral health care services for these groups through publicly funded primary health care in Iran. Moreover, it should be noted that reducing socioeconomic inequalities in dental caries should be accompanied by appropriate health promotion policies that focus actions on the fundamental SES causes of dental disease.…”
Section: Resultsmentioning
confidence: 99%
“…Oral health is one of the main components of general health, which affects quality of life of the population. 1,2 Increasing utilization of dental care services and routine oral checkups could lead to better oral health. 3 Studies have highlighted that socioeconomic status 4 is significantly associated with oral health status.…”
Section: Introductionmentioning
confidence: 99%
“…For example, as the existing studies (e.g., (36)(37)(38)(39)) showed pro-rich inequalities in health care utilization in Iran, it is recommended to expand oral health care services for these groups through publicly funded primary health care in Iran. Moreover, it should be noted that reducing socioeconomic inequalities in oral health should be accompanied by appropriate health promotion policies that focus actions on the fundamental SES causes of dental disease.…”
Section: Resultsmentioning
confidence: 99%